Antifungal Nafuredin and Epithiodiketopiperazine Derivatives From the Mangrove-Derived Fungus Trichoderma harzianum D13 - Zhao, Dong-Lin; Zhang, Xi-Fen; Huang, Rui-Huan; Wang, Dan; Wang, Xiao-Qiang; Li, Yi-Qiang; Zheng, Cai-Juan; Zhang, Peng; Zhang, Cheng-Sheng (Frontiers in Microbiology, 2020)
A new polyketide derivative, nafuredin C (1), a novel heterocyclic dipeptide, trichodermamide G (3), together with four known biogenetically related compounds nafuredin A (2), trichodermamide A (4), aspergillazin A (5), and peniisocoumarin H (6), were isolated from the mangrove-derived fungus Trichoderma harzianum D13. Their structures, including their absolute configurations, were determined by spectroscopic analysis and time-dependent density functional theory-electronic circular dichroism calculations. Trichodermamide G was found to be a novel epithiodiketopiperazine derivative with an unprecedented cyclic system containing a sulphur bridge, and nafuredin C represented the third nafuredin derivative of these homologous compounds. The new compound nafuredin C exhibited obvious antifungal activity against Magnaporthe oryzae with a minimum inhibitory concentration (MIC) of 8.63 μM, which is on the same order of magnitude as the positive control carbendazim (MIC = 3.27 μM).